ISU-ISU SEMASA BIDANGKUASA MAHKAMAH SYARIAH: SATU SOROTAN DALAM KES JENAYAH SYARIAH (LIWAT) - Abdul Rahman, Narizan (Jurnal Syariah, 2019)
The issue regarding jurisdiction of sharF'ah courts in Malaysia is never ending. There have been cases in the past, whereby civil courts interfered with the jurisdiction of shart'ah courts, not to mention those decided after the amendment of Article 121(1) of the Federal Constitution. The amendment took place with the purpose of taking away the civil courts' jurisdiction over matters within the former 's jurisdiction. Recent developm.ent whereby civil courts claiming its' jurisdiction over shari'ah courts in "liwii( case, is totally unbecoming. In truth, there are specific provisions for "liwii(' under every states Enactments and yet the civil courts retained their jurisdiction. This article highlights the "liwii( offence and the issues surrounding the cases decided recently. Whether these cases hampered the amendment to Article 121 (1) of The Federal Constitution or not is yet to be seen.